2022
DOI: 10.1186/s13071-022-05465-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between water, sanitation, and hygiene access and the prevalence of soil-transmitted helminth and schistosome infections in Wolayita, Ethiopia

Abstract: Background The Geshiyaro project is a 5-year intervention to assess the impact of community- and school-based water, sanitation, and hygiene (WaSH) interventions on reducing infection with soil-transmitted helminths (STH) and schistosome parasites in combination with deworming in Wolayita zone, Ethiopia. Methods A population-based, cross-sectional census and parasitological mapping activity was conducted between 2018 and 2019. Individuals in the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…A separate paper has been published on the associations found between WaSH access and the prevalence of STH and SCH found at baseline in the Geshiyaro project [ 19 ]. Definitions for household WaSH status are in line with the World Health Organization and United Nations Children’s Fund (WHO/UNICEF) Joint Monitoring Programme for Water Supply, Sanitation and Hygiene (JMP) guidelines [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…A separate paper has been published on the associations found between WaSH access and the prevalence of STH and SCH found at baseline in the Geshiyaro project [ 19 ]. Definitions for household WaSH status are in line with the World Health Organization and United Nations Children’s Fund (WHO/UNICEF) Joint Monitoring Programme for Water Supply, Sanitation and Hygiene (JMP) guidelines [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…A baseline parasitological mapping survey was conducted in all arms in 2018, to determine the prevalence and intensity of STH infection in the identi ed community, strati ed by age and gender. The baseline data showed low levels of schistosome parasite (both Schistosoma mansoni and Schistosoma haematobium) infection in all study sites by using Kato Katz (KK) diagnostic method (15). The focus of this paper will be on the control of STH infection.…”
Section: Longitudinal Parasitological Sentinel Surveysmentioning
confidence: 99%
“…Every year, hundreds of articles are published on schistosomiasis. Table 2 summarizes the recently reported prevalence of UGS in SSA that was indexed in PubMed [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ,…”
Section: Recent Status Of Ugs In Sub-saharan Africamentioning
confidence: 99%
“…One population-based survey of 19,250 SAC in Benin confirmed that UGS was predominant, with a 17.6% prevalence [ 8 ]. In Ethiopia, a mapping of 15,133 SAC in 2018–2019 reported a prevalence of 0.13% [ 21 ], while Camara et al reported a prevalence of 4.2% among 10,434 SAC in 2014 in Gambia [ 27 ]. Similarly, mapping in Sudan reported a prevalence of 5.2% among 100,726 SAC in 2016–2017 [ 61 ], and a cross-sectional study in Tanzania reported a prevalence of 5.3% through a population-based mapping in 2006–2007 [ 72 ].…”
Section: Recent Status Of Ugs In Sub-saharan Africamentioning
confidence: 99%